Incentives for Environmental Management Accounting Implementation in Finnish Environmentally Sensitive Industries - Taittonen, Anselmi (My University, 2024)
In the current era, businesses are facing increasing pressure to reduce the environmental impact of their activities. For example, the environmental reporting pressures from legislation, investors, and customers are high. Consequently, companies are encouraged to enhance their environmental performance. However, there is still a lack of clarity among companies regarding the intrinsic benefits of environmental performance besides meeting reporting requirements and maintaining the satisfaction of investors and customers. This thesis addresses the topic of environmental management accounting (EMA), which is the counterpart to external environmental reporting. In other words, it refers to the internal use of environmental information. In practice, EMA involves the monitoring and utilization of environmental indicators and costs to inform decision-making and assist in traditional management accounting practices. Researchers have identified a multitude of benefits from EMA, including the reduction and improved allocation of costs, improved accuracy in pricing and evaluation of investment decisions, as well as new possibilities in process and product innovations. This study examines the intrinsic benefits of EMA, which are distinct from those derived from external reporting. The topic was approached from the perspective of institutional theory, which explains the reasons behind organizational behavior in situations where the economic consequences of that behavior are not immediately apparent. In other words, the behavior would be irrational in the absence of institutional pressures that drive the organization towards it. A significant number of studies on EMA have been normative in nature, encouraging companies to implement EMA, often citing the climate crisis. This thesis takes a more critical approach, assessing the usefulness of EMA from a financial perspective. The study involved interviews with accounting and environmental professionals from Finnish companies operating in environmentally sensitive industries. The concept of EMA was relatively unknown to the interviewees, but there were certain practices in the companies that could be characterized as EMA practices. These included the development of new business models and investment decisions based on environmental information. Potential benefits of EMA were also seen in the assessment of environmental costs and the reduction of waste. However, interviewees were uncertain about the financial benefits of EMA and whether any company would adopt its tools without the influence of institutional pressures. The study provides new insights into the challenges of EMA and its dependence on institutional pressures, which have received relatively little attention especially in Finnish research.

Yrityksiin kohdistuu jatkuvasti kasvavia paineita, jotka liittyvät niiden toiminnan ympäristövaikutuksiin. Ympäristöön liittyvät raportointivaatimukset ovat ilmeisiä niin lainsäädännön, sijoittajien kuin asiakkaidenkin suunnalta, ja yrityksiä kannustetaan parantamaan ympäristösuoriutumistaan. Yrityksille voi kuitenkin olla nykytiedon valossa epäselvää, mitä hyötyä ympäristösuoriutumisesta itsessään on lakisääteisten raportointivaatimusten täyttämisen sekä sijoittajien ja asiakkaiden tyytyväisinä pitämisen lisäksi. Tämä tutkielma käsittelee johdon ympäristölaskentatoimea, joka on ulkoisen ympäristöraportoinnin kääntöpuoli eli ympäristöön liittyvän informaation sisäistä hyödyntämistä. Käytännössä tämä tarkoittaa ympäristöindikaattoreiden ja -kustannusten seuraamista ja hyödyntämistä päätöksenteon sekä johdon laskentatoimen perinteisten menetelmien tukena. Johdon ympäristölaskentatoimi tuo yrityksille tutkijoiden mukaan hyötyjä esimerkiksi kustannusten kohdentamisessa ja vähentämisessä, hinnoittelussa, investointipäätösten arvioinnissa sekä prosessi- ja tuoteinnovaatioissa. Tämä tutkimus keskittyy tutkimaan niitä johdon ympäristölaskentatoimen hyötyjä, jotka eivät johdu ulkoisesta raportoinnista. Aihetta lähestyttiin institutionaalisen teorian näkökulmasta, joka selittää, miksi organisaatiot toimivat tietyllä tavalla, vaikka toimintatavan taloudelliset hyödyt eivät olisi ilmeisiä; toisin sanoen toiminta olisi irrationaalista ilman institutionaalisia paineita, jotka tähän toimintaan ohjaavat. Monet johdon ympäristölaskentatoimea käsittelevät tutkimukset ovat olleet luonteeltaan normatiivisia, eli ne pyrkivät kannustamaan yrityksiä johdon ympäristölaskentatoimen käyttöön, yleensä ilmastokriisiin vedoten. Tämän tutkimuksen lähestymistapa on kriittisempi, ja johdon ympäristölaskentatoimen hyödyllisyyttä arvioidaan taloudellisesta näkökulmasta. Tutkimuksessa haastateltiin laskentatoimeen ja ympäristöasioihin erikoistuneita ammattilaisia suomalaisista yrityksistä, joiden toimintaan liittyy merkittäviä ympäristövaikutuksia, toisin sanoen ympäristöllisesti merkittävien toimialojen yrityksistä. Johdon ympäristölaskentatoimi oli haastateltaville käsitteenä melko tuntematon, mutta yrityksissä oli tiettyjä käytäntöjä, joita voidaan luonnehtia termin alle kuuluviksi. Yritykset olivat muun muassa kehittäneet uusia liiketoimintamalleja ja tehneet investointipäätöksiä ympäristöinformaatioon perustuen. Potentiaalisia hyötyjä nähtiin myös ympäristökustannusten arvioinnissa ja hukan vähentämisessä. Haastateltavat olivat kuitenkin epävarmoja johdon ympäristölaskentatoimen taloudellisten hyötyjen arvioinnista ja siitä, ottaisiko mikään yritys sen työkaluja käyttöön ilman institutionaalisten paineiden vaikutusta. Tutkimus tuo esiin uusia näkökulmia johdon ympäristölaskentatoimen haasteista sekä riippuvuudesta ulkoisiin paineisiin, jotka ovat aiheina saaneet varsinkin suomalaisessa tutkimuksessa melko vähän huomiota.
Keywords: environmental management accounting, environmentally sensitive industries, institutional pressures, johdon ympäristölaskentatoimi, ympäristöllisesti merkittävät toimialat, institutionaaliset paineet